Development of Video Tutorials on Drawing Female Body Anatomy for Students of Class X SMK Pembangunan Bagan Batu - Aulia, Tiara; Efi, Agusti (Gorga : Jurnal Seni Rupa, 2024)
The teaching and learning process of body anatomy drawing material in the Class X Fashion Basics subject at SMK Pembangunan is not in accordance with the expected learning outcomes. Researchers offer alternative learning media in video tutorial development research on drawing female body anatomy which aims to: 1). Develop a video tutorial for drawing female body anatomy in comparison to 11 x head height. 2). Test the validity and practicality of video tutorials for drawing female body anatomy in comparison to 11 x head height. This study used the 4D model research and development (R&D) method, which consists of four stages: define, design, and development. The dissemination stage was not conducted due to the limited research. Data in this study were collected through observation, interview, and questionnaire. This study conducted a feasibility test with the results of the media expert validation test with a very valid category. Validation by material experts with a very valid category. The results of the practicality assessment of students in two large groups with very practical and small categories with very practical categories. So that video tutorials for drawing female body anatomy can be utilized in teaching and learning activities.